2022
DOI: 10.17559/tv-20220321074430
|View full text |Cite
|
Sign up to set email alerts
|

Structural Integrity - Historical Context

Abstract: In this paper the focus is on a historic context of a few milestones in the development of structural integrity, which closely follow development of human civilization. Starting from the Great Pyramids in ancient Egypt, this story leads us through the history of stone, concrete and metal constructions as follows: Hagia Sophia, stone (Mostar) and iron (Shropshire) bridges, skyscrapers (Eiffel tower, Burj Khalifa) and sky reaching airplanes (Airbus A380). In each case, the most important aspects of structural in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Semi-arch shapes were varied, along with the changes in the cross-sections along the arch lengths. Adopted arches were slightly stronger than the ones shown in [1,6], with a parabolic arch. It was determined that the reaction forces in the semi-arches from the dome dead weight acting on the main support ring was 1050 kN, i.e.…”
Section: Numerical Simulations Of the Dome As A Wholementioning
confidence: 63%
See 1 more Smart Citation
“…Semi-arch shapes were varied, along with the changes in the cross-sections along the arch lengths. Adopted arches were slightly stronger than the ones shown in [1,6], with a parabolic arch. It was determined that the reaction forces in the semi-arches from the dome dead weight acting on the main support ring was 1050 kN, i.e.…”
Section: Numerical Simulations Of the Dome As A Wholementioning
confidence: 63%
“…hrough the history of a mankind, large structures were always a demonstration of power and human ingenuity to make them bigger and bigger, but also more reliable at the same time, [1]. Concrete was always a suitable material for large structures, due to its low price and satisfying mechanical properties, except for the tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Metal bridges were not known in ancient times. There are only indications that in ancient China and India, around the 1st century AD, iron chains were used for suspension bridges (Bender, 1872;Sedmak, Ković, & Kirin, 2022;).…”
Section: Results and Discussion What Materials Were Used At Different...mentioning
confidence: 99%
“…The first real metal bridge was built in the central industrial region of England, in the county of Shropshire across the river. River Severn (Sedmak, Ković, & Kirin, 2022). On one side of the river was the famous Coalbrookdale works of Abraham Darby II and Reynolds.…”
Section: Results and Discussion What Materials Were Used At Different...mentioning
confidence: 99%
“…Consequently, HSLA steel was used, SUMITEN 80P, with YS around 700 MPa, but only after extensive experimental research of the prototype, as shown in Figure 1, to prove its fitness-for-purpose, as described in [21,22]. Later on, this approach was named the structural integrity [25]. Although this issue was a topic of a number of papers decades ago, only recently some of the most intriguing results have been explained in detail by using the finite element method for precise analysis of the stress-strain state, both for the prototype [26][27][28] and for tensile panels with large and small cracks, as shown in [29,30] for the BM.…”
Section: Introductionmentioning
confidence: 99%